BUDIDAYA DURIAN MONTHONG GUNA MEMANFAATKAN LAHAN TERLANTAR BAGI MASYARAKAT BALAI GADANG DI KOTA PADANG - Sari, Afrima; Gustian, Gustian; Febjislami, Shalati; Sutoyo, Sutoyo; Ramadhan, Nugraha; Hariandi, Doni (LPPM Universitas Andalas, 2025)
Banda Langik Women Farmers Group (KWT Banda Langik) is an active women-led farming group in Padang City, established based on shared goals, harmony, and a spirit of collaboration in optimizing the use of agricultural resources. The group owns idle land and unused home yards that have not been utilized optimally. Through this community service activity, Monthong durian seedlings were planted to transform inactive land into productive economic assets while also providing the group with knowledge on durian cultivation. This activity was carried out from May to September 2023 using survey, discussion, and demonstration methods for planting Monthong durian on KWT Banda Langik's land. The seedlings were sourced from the Horticultural Plant Seed Center (Balai Benih Induk Tanaman Hortikultura) located on Jalan Pertanian, Lubuk Minturun, Kota Padang with a quality rating of 80%. One hundred twenty seedlings were distributed to the group-5 were planted on the group's shared land. At the same time, the remaining 115 were given to individual members, each receiving 10 seedlings to plant in their home yards or on personal land. Monthong durian is categorized as an early-bearing plant with a relatively short trunk height of 4–5 meters, which offers a significant advantage in harvest time compared to local durian varieties. The cultivation of Monthong durian, as a form of community empowerment, has successfully enhanced the understanding and skills of the KWT members in managing land effectively by planting high-economic-value crops that are also popular among the public.